2023
DOI: 10.7554/elife.81320
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity blunts antimicrobial responses in fetal monocytes

Abstract: Maternal pre-pregnancy (pregravid) obesity is associated with adverse outcomes for both mother and offspring. Amongst the complications for the offspring is increased susceptibility and severity of neonatal infections necessitating admission to the intensive care unit, notably bacterial sepsis and enterocolitis. Previous studies have reported aberrant responses to LPS and polyclonal stimulation by umbilical cord blood monocytes that were mediated by alterations in the epigenome. In this study, we show that pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…Specifically, the IPA analysis implicated activation of Fcψ-receptor mediated Phagocytosis in obesity-exposed microglia and HBC clusters, but suppression of Neuroinflammation Signaling Pathway (Fig 3E,F). This mixed picture of both macrophage activation and exhaustion in the setting of maternal immune activation is consistent with and extends published results, which describe not only fetal macrophage priming, activation and increased phagocytosis 22,23 in response to maternal obesity and other maternal immune-activating exposures, but also macrophage and monocyte exhaustion phenotypes 65,66 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, the IPA analysis implicated activation of Fcψ-receptor mediated Phagocytosis in obesity-exposed microglia and HBC clusters, but suppression of Neuroinflammation Signaling Pathway (Fig 3E,F). This mixed picture of both macrophage activation and exhaustion in the setting of maternal immune activation is consistent with and extends published results, which describe not only fetal macrophage priming, activation and increased phagocytosis 22,23 in response to maternal obesity and other maternal immune-activating exposures, but also macrophage and monocyte exhaustion phenotypes 65,66 .…”
Section: Resultssupporting
confidence: 92%
“…Our lab previously reported that obesity primed Mg and HBCs toward a pro-inflammatory phenotype when treated with LPS 23 . More recent studies show that macrophage and monocyte exhaustion plays a role in obesity-associated cellular programming 66 .…”
Section: Discussionmentioning
confidence: 99%
“…LNs were collected into ice‐cold FACS buffer, diced with scalpels, mashed through a 70‐μm filter, and processed for cell isolation as described for WAT. Blood samples were collected in EDTA‐treated tubes and peripheral blood mononuclear cells (PBMCs) were isolated by centrifugation at 2000 rpm (800 × g ) for 30 min using a Lymphoprep gradient (STEMCELL Technologies) as described 21 …”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected in EDTA-treated tubes and peripheral blood mononuclear cells (PBMCs) were isolated by centrifugation at 2000 rpm (800 × g) for 30 min using a Lymphoprep gradient (STEMCELL Technologies) as described. 21…”
Section: Cell Isolation and Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation